Meryl Saxton: capstone - Saxton, Meryl, artist (Colorado State University. Libraries, 2018)
The artist's statement: I like to explore the possibilities of how to present visual problems. Using computer programs and traditional mediums I can figure out what is best suited for a project. I enjoy experimenting with rich textures, vibrant colors, and whimsical/fantastical subject matter. Instead of adapting a subject to my style I like to adapt my style to the subject or the message; It's a puzzle to solve and everything requires something a little bit different.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design